Fetal neurodevelopmental recovery in donors after laser surgery for twin‐twin transfusion syndrome. (26th November 2020) - Rajagopalan, Vidya; Ashouri, Karam; Llanes, Arlyn; Vanderbilt, Douglas L.; Lepore, Natasha; Bluml, Stefan; Lai, Hollie A.; Wisnowski, Jessica; Chon, Andrew H.; Chmait, Ramen H.
Abstract: Background: Fetal magnetic resonance imaging (MRI) and spectroscopy (MRS) provide a unique opportunity to non‐invasively measure markers of neurodevelopment in survivors of twin‐twin transfusion syndrome (TTTS). Objective: To characterize fetal brain maturation after laser surgery for TTTS by measuring brain volumes and cerebral metabolite concentrations using fetal MRI + MRS. Study Design: Prospective study of dual surviving fetuses treated with laser surgery for TTTS. At 4–5 postoperative weeks, fetal MRI was used together with novel image analysis to automatically extract major brain tissue volumes. Fetal MRS was used to measure major metabolite concentrations in the fetal brain. Results: Twenty‐one twin pairs were studied. The average (±SD) gestational age at MRI was 25.89 (±2.37) weeks. Total brain volume (TBV) was lower in the donors, although cerebral volumes were not different between twin pairs. Recipients showed lower proportions of cortical and cerebellar volumes, normalized to TBV and cerebral volumes. MRS data showed that biochemical differences between twin brains were related to discrepancy in their brain volumes. Conclusion: Although donors have a smaller TBV compared to recipients, proportionality of brain tissue volumes are preserved in donors. MRS maturational markers of fetal brain development show that recovery in donors persists 4 weeks after surgery.